Analytical Method for the Validation of Three Polyphenols as a Marker Compound for the Standardization of Solidago virgaurea subsp. gigantea Extracts and Antiadipogenesis of Harvesting Time and Location - Seung Hwan Hwang; Ju Hee Kim; Zhiqiang Wang; Jae-Yong Lee; Soon Sung Lim (Journal of Analytical Methods in Chemistry, 2017)
Protocatechuic acid (PC), chlorogenic acid (CA), and kaempferol-3-O-rutinoside (K-O-R), isolated from the Solidago virgaurea subsp. gigantea (SV) extract, were quickly and efficiently separated using HPLC. Our chromatographic method was found to effectively separate PC, CA, and K-O-R at retention times of 5.36, 8.22, and 17.04 min, respectively. Linearity of PC, CA, and K-O-R was found to be in the range of 4.85–485.00, 47.5–1900.00, and 8.50–850.00 μg/ml. Recoveries ranged between 101.32 and 103.30%, 95.82 and 100.25%, and 96.18 and 99.37%, for PC, CA, and K-O-R, respectively. The antiadipogenesis activity of SV extracts collected from five different months and from seven different regions was evaluated using an Oil Red O staining assay in 3T3-L1 cells. Extract from SV collected in April from the Ulleung Island produced over 106.89% inhibition of adipogenesis without cytotoxicity at 50 μg/ml. This extract had a high amount of PC and K-O-R. The developed HPLC method was found to be fast, accurate, precise, and reproducible and could be applied to qualitative and quantitative analysis of three bioactive compounds in SV extracts. The SV extract collected in April from Ulleung Island can be used as a functional food ingredient preventing obesity.